Dendrophthora costaricensis (Loranthaceae), a new record for the flora of Mexico - Cházaro Basáñez, Miguel; Oliva Rivera, Héctor (Instituto de Ecología, A.C., 1991)
Dendrophthora costaricensis Urban, is recorded from México for the first time. It was found on the seaward slopes of Cofre de Perote volcano in central Veracruz, México.